Factors Associated With Physician Empowerment and Well-being at an Academic Medical Center. Issue 7 (July 2020) - Yakes, Elizabeth Ann; Dean, Stephanie; Labadie, Robert F.; Byrne, Daniel; Estrada, Cristina; Thompson, Reid; Kendall, James; Yarbrough, Mary
Abstract : Objective: This study reports an institutional approach to rapidly measure burnout and gather physicians' opinions on workplace factors that empower well-being. Methods: In July 2017, physicians at Vanderbilt University Medical Center were invited to participate in a two-question survey measuring self-reported burnout and providing an opportunity to describe structures that empower well-being. Free-text responses were analyzed and a linear regression model assessed factors associated with well-being. Results: A total of 1135 physicians responded (43.3% response rate) with a mean well-being score of 56 (scale 0 to 100). Higher scores were associated with clinical fellow status ( P  = 0.002), male sex ( P  = 0.008), less allocation of time to clinical care ( P  < 0.001), and not commenting on "leadership" and "autonomy" in the free-text response. Conclusions: Brief surveys collecting perspectives on well-being can help employers identify high-risk groups and provide a roadmap for institutional change.